Science-policy engagement in the context of tracking agriculture adaptation - Njuguna, Lucy (2024)
The presentation shares key lessons from engaging with policymakers to strengthen their ability to track and report on climate change adaptation. It was delivered during a webinar hosted by the International Network of Boundary Organizations on Adaptation, aimed at improving policy engagement to accelerate climate adaptation efforts.